POPULATION STRUCTURE OF Acanthaster planci ON THE REEF FLAT AT THE SOUTHERN PART OF BUNAKEN ISLAND - Napitupulu, Patritia; Tioho, Hanny; Windarto, Agung (Sam Ratulangi University, 2013)
The information on population structure of Acanthaster planci in Bunaken National Park (BNP) is urgent to be presented in order to be considered in decision making especially on coral reef management in BNP. The objectives of this study was to examine the population structure of A. planci, represented by the diameter and weight, number of arms, while the density, distribution and types of coral predation by reef animals in the Southern part of Bunaken Island also observed. Data were collected at the three locations namely, front reef flat (FRF), middle reef flat (MRF) and back reef flat (BRF) with total coverage area of ​​100 x 50 meters. Sixty two individuals (41 at night and 21 at day time) were found with a body diameter ranging between 14 – 28 cm, whereas body weight ranged from 80 – 700 gr, with the number of arms between 9 until 17. The density of A. planci during day time was 0.0042 ind/m2, while the night time was 0.0082 ind/m2, moreover the animal is generally spread aggregated. The results of this study indicated that the population of A. planci in BNP was an adult population with density is still relatively normal, despite an alert sign for the sustainability of coral reef ecosystems in the BNP.